2022
DOI: 10.3390/cimb44110352
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory and Hypouricemic Effect of Bioactive Compounds: Molecular Evidence and Potential Application in the Management of Gout

Abstract: Gout is caused by the deposition of monosodium urate crystals in the joint and represents the most common form of inflammatory arthritis in men. Its prevalence is rising worldwide mainly due to the increase of risk factors associated with the disease, in particular hyperuricemia. Besides gout, hyperuricemia leads to an increased inflammatory state of the body with consequent increased risk of comorbidities such as cardiovascular diseases. Increasing evidence shows that bioactive compounds have a significant ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 108 publications
0
8
0
Order By: Relevance
“…However, large interspecies difference in the expression of metabolic enzymes and drug elimination pathways, which influence both drug pharmacokinetics and pharmacology, requires careful selection of the animal model. Several animal models of arthritis, either experimentally induced or spontaneous, have been developed that significantly contributed to understanding disease pathogenesis and permitted evaluation of new potential anti-arthritic agents, despite no single animal model being able to fully replicate all the clinical features of human arthritis [ 7 , 41 , 42 , 43 , 44 , 45 ]. Both spontaneous and induced animal models of arthritis are available.…”
Section: Animal Models Of Arthritismentioning
confidence: 99%
See 3 more Smart Citations
“…However, large interspecies difference in the expression of metabolic enzymes and drug elimination pathways, which influence both drug pharmacokinetics and pharmacology, requires careful selection of the animal model. Several animal models of arthritis, either experimentally induced or spontaneous, have been developed that significantly contributed to understanding disease pathogenesis and permitted evaluation of new potential anti-arthritic agents, despite no single animal model being able to fully replicate all the clinical features of human arthritis [ 7 , 41 , 42 , 43 , 44 , 45 ]. Both spontaneous and induced animal models of arthritis are available.…”
Section: Animal Models Of Arthritismentioning
confidence: 99%
“…Therefore, induced models of arthritis are preferable for the assessment of anti-arthritic agents. These models involve mechanically induced joint destabilization or chemical treatment, usually by intra-articular injection of the chemical agent, causing an inflammatory reaction that mimics arthritis development [ 7 , 41 , 42 , 44 , 45 ]. The knee is the joint most often employed in animal models of arthritis [ 41 , 42 ].…”
Section: Animal Models Of Arthritismentioning
confidence: 99%
See 2 more Smart Citations
“…Gout is one of the relatively common inflammatory diseases of the joints caused by the deposition of uric acid crystals in the tissues, in which uric acid is produced by xanthine oxidase (XO) acting on the purine bases hypoxanthine and xanthin . In developed countries, the prevalence of gout is 3–6% in males and 1–2% in females, with a strong impact on individual health and healthcare systems . Studies in recent years have shown that gout is an independent risk factor for chronic kidney disease, hypertension, cardiovascular and cerebrovascular diseases, diabetes, and an independent predictor of premature death. , …”
Section: Introductionmentioning
confidence: 99%